Pseudo-judicial Review for the Dispute over the Result of the Regional Head Election in Indonesia - Indra, Mexsasai; Saragih, Geofani Milthree; Handoko, Tito (Lentera Hukum, 2023)
In Indonesia, the Constitutional Court has the power to decide the dispute over the result of the national election, including that of the regional head election. In practice, the Constitutional Court exercises power with the so-called pseudo-judicial review for the result of the regional election dispute. This study aims to analyse the rationale of the Constitutional Court to implement a pseudo-judicial review over the regional head election result, given the judicial activism that also is limited to checks and balances. It also links the theoretical basis for rule-breaking and judicial activism by the Constitutional Court, the transition of the Constitutional Court's power in deciding regional election disputes from temporary to permanent, as well as further analysis of why the Constitutional Court needs to file a lawsuit for review. This study used legal research that examined legal principles and regulations with a theoretical approach analysed qualitatively. The results of this study indicate that pseudo-judicial review affirms the legal breakthrough beyond ordinary decisions as this was made on the ground of the public interest. While the Constitutional Court is essential in maintaining and overseeing democracy in Indonesia, the rationale of the Constitutional Court under the public interest is justified as it is constitutionally correct that has led to judicial activism. A pseudo-judicial review is for substantial justice and can influence time efficiency.Keywords: Constitutional Court, Judicial Review, Local Election Disputes.